Technological capability building through backward linkages in the Malaysian petrochemical industry / Zakariah Abdullah - Zakariah, Abdullah (2012)
While foreign direct investment (FDI) is regarded as an effective channel of technology transfer, the question of whether or not FDI helps to upgrade the technological capacities of firms in host countries remains an important one for policy makers. The study presented here is based on a firm-level analysis of petrochemical firms in two Malaysian industrial regions, namely Pasir Gudang in Johor, and Gebeng in Pahang. This research is concerned with technological capability of local suppliers in the petrochemical industry in Malaysia. The technological capabilities of local suppliers are assumed to have been upgraded by the backward linkages provided by the multinational company (MNC) subsidiaries that located in Malaysia after the country decided to host petrochemical plant in the 1970s. Together with the country’s national oil company, Petroliam Nasional Berhad (Petronas), MNC subsidiaries played a key role in bringing the technology of the petrochemical industry to Malaysia in the 1980s. Studies indicate that MNCs are playing a crucial role in the current globalization process and are expected to increase their control over productive activities in many countries, especially in Malaysia’s part of the world. They are expected to increase their activities in the foreseeable future. The research questions of this study deal with the variables that affect the diversity of backward linkages between subsidiaries and local suppliers. Factors explored include the corporate strategy of MNCs, the technological capability of local suppliers, inter-organizational linkages between MNCs and local suppliers, and other specific factors, such as the ownership structure and size of MNCs. This study utilizes an interview survey of MNC subsidiaries and local suppliers in the Malaysian petrochemical industry to explore the factors influencing the upgrading of technological capability of local suppliers through backward linkages. A total of 9 MNCs and 18 local suppliers have so far participated in the survey. (This is based on the population of 27 MNCs in the Malaysian petrochemical industry in the two regions surveyed. Some firms are reluctant to participate). The findings suggest that the roles of MNCs located in Malaysia have shifted. They have developed a higher level of autonomy. This has increased the diversity of backward linkages offered to local suppliers. However, the number of backward linkages formed is still dependent on the ownership structure of the firms. Wholly local-owned MNCs have more strength in backward linkages than joint ventures, which in turn are stronger in backward linkages than wholly foreign-owned MNCs. MNCs that are wholly foreign-owned do not produce as many linkages as other companies unless they are embedded in the host country. Thus, backward linkages provided by subsidiaries can significantly affect local suppliers’ technological capabilities. At the same time, the motivation of MNCs to create backward linkages is positively affected by their production networking, and the diversity of backward linkages they create is believed to be affected by the specific roles the subsidiaries play, rather than by the nationality of the firms involved. Local firms in developing countries find themselves in a weak position when bargaining with MNCs. Support from the government, industry associations or international organizations can contribute to improving their bargaining position (Lauridsen, 2004). In the case of Malaysia, Petronas as the anchor company for the Vendor Development Program (VDP) has become a tool for technology transfer. Petronas has brought technology into Malaysia and has become an enabler for the country to upgrade the technological capabilities of local suppliers in the petrochemical industry. In this regard, Petronas has acted as an intermediary in bargaining by local suppliers.